Detection and Reduction of Aflatoxin and Orchratoxin A in Black and White Pepper - Jalili, Maryam (2010)
Despite the serious side effects of aflatoxins (AFs) and ochratoxin A (OTA) on human health, there is no published method for the reduction of AFs and OTA in black and white peppers. In light of this, this thesis describes methods that can be used to reduce AFs and OTA in black and white peppers. The separation and quantification of OTA by high performance liquid chromatography (HPLC) in black and white peppers was optimized. The influence of three variables: type of solvent, solvent-volume-to-sample-size (v/w), and amount of sodium chloride (NaCl) (g) on recovery of OTA was evaluated. The response surface methodology (RSM) was applied to determine the optimum amount of NaCl and solventvolume-to-sample-size on the extraction of OTA from black and white peppers. This optimized method proved to be reliable with recovery values ranging from 94.3 to 102.0%. In order to assess occurrence of AFs and OTA in pepper commercialized in Malaysia, samples of black and white pepper were randomly collected from supermarkets and wholesales located in Peninsular Malaysia. Results showed that 58.3 and 67.5% of samples were contaminated with AFs and OTA, with concentrations ranging from 0.1- 25.8 and 0.30-33.0 ng/g, respectively. In order to reduce AFs and OTA in black and white pepper, a method was established by using gamma ray at doses within the range 5 to 30 kGy at 12 and 18% p pper moisture contents. Results showed that the method could not completely reduce OTA and AFs even at dose of 30 kGy and 18% moisture content. The second method proposed applied chemical compounds including acids, alkalis, salts and oxidizing agents for reduction of AFs and OTA. The highest reduction (41.9 – 57.3%) was obtained by using alkaline compounds. This study also optimized a method for reducing AFs and OTA in white pepper. The RSM was used to evaluate the effect of four variables, i.e., time (20-60 min), temperature (30-70 ºC), calcium hydroxide (0-1%) and hydrogen peroxide (1-3%), on reducing AFs and OTA during soaking. A treatment time of 57.8 min, temperature of 62 ºC, calcium hydroxide concentration of 0.6% (w/v), and hydrogen peroxide concentration of 2.8% (v/v) were found to be the optimum conditions for achieving the highest value of mycotoxin reduction and the best value for color. Maximum reduction at the optimum conditions ranged from 70.7 for AFB2 to 100% for AFG1, respectively. Since hydrogen peroxide caused damage to the surfaces of black pepper, this method was not applicable for black pepper. Therefore, the effect of sodium hydrosulfite at different concentrations (0.25, 0.5, 1, 1.5 and 2%) during boiling and sterilization was investigated. The boiling was done at 100 °C and atmospheric pressure for 30 min while sterilization was done under high pressure (1.5 bar) and 121 ºC for 15 min. The maximum reductions were obtained by applying sterilization at 2% of Na2S2O4 and corresponded to 96.0, 96.1, 77.7, 100% and 100% for OTA, AFB1, AFB2, AFG1 and AFG2, respectively. By applying these methods to black and white peppers,more than 95% reduction of OTA and the aflatoxins B1, and G1, which are the most dangerous mycotoxins, was obtained.